(untitled) (Damascus University Journal for legal sciences, 2025)
The Islamic Sharia guarantees the freedom of choice for the taxpayer in all his words and actions, and made consent the basis for his verbal and actual actions, and out of keenness to guarantee freedom of thought, it prohibited everything that leads to transgressing a person’s consent and forcing him to do or say something he does not want, and among the greatest of these: coercion to change religion, And forcing people to believe something they are not convinced of. This research will define the concept of coercion, explain its types and conditions, mention the rule of compulsion to enter Islam, If the apostate is forced to convert to Islam, will the apostate be punished or not? This is due to the strength of the evidence.